Washington View: Money doesn't buy easy answers. (October 2021) - Ferguson, Maria
In response to the COVID-19 pandemic, the U.S. Congress has allocated just under 190 billion to support K-12 education. As Maria Ferguson explains, these much-needed funds will require states and districts to make plans for how best to use them, and the planning process is complicated in districts that are already stretched and facing unpredictable circumstances. The plans that have been submitted so far vary in their level of detail, but common themes include the effects of the pandemic on student achievement and the mental health needs of both students and school staff .